Analisis Dampak Perusahaan Samsung Terhadap Pendapatan Nasional Di Indonesia - Nabilla Anggun Al Husna; Della Maurellia; Verdy Hermanto Pratama; Jesica Jesica; Ni Wayan Luh Nova Ratna Sari; Dwi Hasmidyani; Muhammad Akbar Budiman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research analyzes the impact of the multinational company Samsung Electronics Co., Ltd. Against national income in Indonesia. Using secondary research methods, data from various sources, including the Central Statistics Agency, Samsung’s financial reports, market studies,and previous academic research, was analyzed to understand Samsung’s contribution to the Indonesian economy. The analysis results show that Samsung’s presence has made a significant contribution to Indonesia’s economic growth through foreign direct investment, jobcreation, increased exports and tax contributions. Apart from that, positive impacts are also felt through the development of supporting industries, increasing human resource capacity, and support for the MSME sector. However, it is also necessary to pay attention to negative impacts such as unhealthy competition and the potential for market domination. Therefore, appropriate regulatory and supervisory measures are needed to maximize the positive impact and minimize the negative impact of Samsung’s presence. Overall, Samsung’s role in driving the Indonesian economy to wards more advanced and sustainable grow this very significant. Collaboration between companies, government and society needs to be improved to ensure the benefits are felt fairly and sustainably.